The Literary in Narrating Dramatic Life Experiences - Hatavara, Mari; Hyvärinen, Matti; Mildorf, Jarmila (The Routledge Companion to Literary Media)

Poeticity and Parody: The Literary Interview on Radio and Podcast - Mildorf, Jarmila (The Routledge Companion to Literary Media)

Narrative and Mental Health: Reimagining Theory and Practice

Abstract Reflection in Contemporary Fiction (Anglia)

Life Storying in Oral History: Fictional Contamination and Literary Complexity - Mildorf, Jarmila

Introduction: Abstract Reflection in Contemporary Fiction - Haekel, Ralf; Butter, Stella; Mildorf, Jarmila (Anglia)

„So viel Größenwahn muss sein!“ Kinderliteratur – Schule – Gesellschaft

Die ‚Tänzerin‘ als hermeneutische Spielfigur. Studierende begegnen einem Gedicht Salah Naouras in der Gedankenhöhle. - Kanning, Julian (Salah Naoura. Paderborner Kinderliteraturtage 2022, Bielefelder Poet in Residence 2022)

Datenbasierte Fähigkeitsprofile im Physikdidaktischen Wissen - Zeller, Jannis; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

The canonical amoebot model: algorithms and concurrency control - Daymude, Joshua J.; Richa, Andréa W.; Scheideler, Christian (Distributed Comput.)

Chasing the American Dream: Chances and challenges of immigrant families – a media task - Intveen, Julie (Englisch betrifft uns)

The United Kingdom: A Multicultural Society Education as a key to life in mixed communities - Bauer, Maike; Intveen, Julie (Englisch Betrifft Uns)

The Royal Divide - Exploring the impact of Megxit on the future of the British monarchy - Bauer, Maike; Intveen, Julie (Englisch Betrifft Uns)

Emotional Debiasing Explanations for Decisions in HCI - Schütze, Christian; Lammert, Olesja; Richter, Birte; Thommes, Kirsten; Wrede, Britta (Artificial Intelligence in HCI)

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Hardware-in-the-Loop-Simulation von HD-Scheinwerfer-Steuergeräten zur Entwicklung von Lichtfunktionen in virtuellen Nachtfahrten - Rüddenklau, Nico

Entwurf und Analyse modellprädiktiver Regelungsansätze zur Steigerung des Immersionsempfindens in interaktiven Fahrsimulationen - Biemelt, Patrick

Lerngegenstand „Doppelkonsonanz“ in der Grundschule: Explizites und implizites Lernen im Längsschnitt. - Topalović, Elvira; Drepper, Laura; Härtel, Kira (Lesen- und Schreibenlernen im Spannungsfeld zwischen Wissen und Können)

Grammatische Modelle (Der Deutschunterricht)

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, Andrey N.; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina
Dataset of the publication "Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field" H. Rose, A. N. Vasil’ev, O. V. Tikhonova, T. Meier, and P. R. Sharapova, Phys. Rev. A 107, 013703 (2023). ( https://doi.org/10.1103/PhysRevA.107.013703 ). The zip file includes the data on which the plots shown in figures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 are based.